Reversal of Migration Flows: A Fresh Look at the German Reunification - Volker Grossmann; Andreas Schäfer; Thomas Steger; Benjamin Fuchs (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
We investigate the dynamic effects of interregional labor market integration on migration flows, capital formation, and the price for housing services. The co-evolution of these variables depends on initial conditions at the time of labormarket integration. In an initially capital-poor economy, there may be a reversal of migration flows during the transition to the steady state, while housing costs are increasing over time. Although capital may accumulate while labor emigrates early in the transition, the causal effect of immigration on capital investments and housing costs is positive. We present new data on the evolution of net migration flows and rental rates for housing in East Germany after 1990. Our results are consistent with the presented evidence in the reverse migration scenario.
Keywords: D90; F20; O10; 330; Capital formation; German reunification; Housing services; Labor market integration; Reverse migration